Pengendalian cacat fisik ikan sarden kaleng menggunakan metode statistical quality control (SQC): Physical defect control in canned sardine fish using statistical quality control (SQC) method - Astiana, Ika; Cesrany, Mahaldika; Gunawan, Rosa Hendri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Statistical Quality Control (SQC) is a quality management approach that uses statistical methods to resolve issues within an organization. This study aimed to determine the extent of physical damage to the end product in fish canning companies and to enumerate the factors contributing to the issue. The data collection methods employed at one of the fish canning companies in Banyuwangi were interviews, observations, and documentation. The evaluation period spanned three months, during which a total of 30 days was dedicated to the examination process. The item in question was a small-sized can, weighing 155 g, produced during the morning shift. The SQC analysis procedure utilized five instruments: examination sheets, histograms, control charts, Pareto diagrams, and cause and effect diagrams. The investigation outcomes indicated that over a period of 30 days, 3,288,138 sardine cans were produced, yielding 5,664 detected product defects. The proportion of sardine product defects was 77% dented items, 17% scratched products, 5% leaky containers, 0.9% bulging items prior to incubation, and 0.1% bulging products following incubation. A study of the control chart for a period of nine days revealed that the quantity of defective canned goods surpassed the upper control limit on inspection days 4, 5, 7, 14, 17, 20, 24, 25, and 27.The root causes of sardine product defects are (1) the absence of written work instructions in the production room, (2) inadequate machine control, (3) irregular machine maintenance, (4) inflating cans, and (5) negligence on the part of employees in performing their work duties.